2019
DOI: 10.3727/108354219x15652651367424
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Service Quality of Airbnb

Abstract: Airbnb has become a strong competitor for hotels when it comes to accommodation choices. However, few studies have analyzed the service quality provided by Airbnb. In order to approach this gap and to support the industry to maintain competitiveness, this study identified related dimensions measuring the service quality based on a qualitative design, conducting a content analysis of Airbnbrelated reviews. The following six dimensions are identified and discussed: Accuracy, Cleanliness, Rooms and Facilities, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Their findings indicated that Airbnb has multiple SQ attributes associated with website, host and facility that produce distinctive effects on customer satisfaction. Sun et al (2019) based on a qualitative design identified accuracy, cleanliness, rooms and facilities, location, personalized service and value as the six dimensions of measuring Airbnb SQ.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings indicated that Airbnb has multiple SQ attributes associated with website, host and facility that produce distinctive effects on customer satisfaction. Sun et al (2019) based on a qualitative design identified accuracy, cleanliness, rooms and facilities, location, personalized service and value as the six dimensions of measuring Airbnb SQ.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although a limited number of research papers have explored the whole SQ concept of Airbnb, there are some studies that considered just some of service-related factors separately, including peer-to-peer interactions (Moon et al , 2019), quality and quantity attributes of hosts (Sun et al , 2019), transaction experience (Liang et al , 2018), trust (Ert and Fleischer, 2019), value co-creation (Jeannette and Barbara, 2017), hospitality experience (Sthapit and Jiménez-Barreto, 2018) and customer experience and review system (Cheng and Jin, 2019). Table 1 summarizes the service-related attributes of Airbnb which have been reviewed through analysis of the available literature to date.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a complementary line of research, Barber and Scarcelli (2010) identified cleanliness as an influencing factor of the perceived service quality. The more recent studies by Sun et al (2019) and Lari et al (2020) corroborate such finding by exploring two major online hospitality platforms, Airbnb and TripAdvisor, respectively. Additionally, since airport hotels are intrinsically connected to airports, issues related to transportation to the city center as well as flight related issues are also highly relevant from a service quality perspective (Tam et al, 2008).…”
Section: 2perceived Hotel Service Qualitymentioning
confidence: 62%
“…e check-in score indicates whether the user is satisfied with the check-in process upon arrival. According to Ranjbari et al and Sun et al [46,61], this indicator is considered among the key points of customer satisfaction with the quality of service offered by Airbnb.…”
Section: Check-inmentioning
confidence: 99%